Integrating Adaptive Functionality in a LMS - van der Sluijs, Kees; Höver, Kai Michael (International Journal of Emerging Technologies in Learning (iJET), 2009)
Learning management systems are becoming more and more important in the learning process in both educational and corporate settings. They can nowadays even be used to server actual courses to the learner. However, one important feature is lacking in learning management systems: personalization. In this paper we look into this issue of personalization that enables courses to be adapted to the knowledge level and learning preferences of the user. We shortly review the state of the art in adaptive systems that allow creating adaptive courses. Then, exemplified in the popular LMS called CLIX we look at the authoring of an adaptive Business English course. We demonstrate how such a static course can be made adaptive by using the GALE adaptive engine. We then show that GALE can be integrated into CLIX, and in other LMSs as well, so that personalization and adaptation can become widely established technology.